Profiling customers against characteristics of corporate responses to complaints. - Lim, Shing Yee. (2008)
This research attempts to draw a link between these two areas of study and find relationships between a number of variables and some aspects of corporate responses. Specifically, it attempts to find out what consumers look for in corporate responses via profiling.